(untitled) (Eurasian Scientific Herald, 2023)
The article contains information about the physiology of the hemostatic system and its components, and discusses the connection between the hemostatic system and inflammation. The physiology of normal hemostasis, the interaction of platelets with endothelial cells and leukocytes, as well as with von Willebrand factor and the complement system and their role in rheumatoid arthritis are described